The Use of Translation Strategy and Translation Methods in Tourism Texts under the Guidance of Peter Newmark’s Translation Theory: A Case Study of Everglades National Park, Florida - Xiao, Liu (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2023)
With the rapid growth of the economy, people's pursuit of quality life is gradually increasing. Travelling abroad has become a hot topic nowadays. The rapid development of overseas travel has increased the demand for tourism translation and more stringent requirements for tourism translators. How to deal with the translation problems caused by the cultural differences between Chinese and English during the translation process is very important to improve the quality of tourism translation. The communicative translation strategy in Newmark's translation theory focuses on the effect that the translation brings to the target language readers, which is of certain guiding significance to the E-C translation of tourism texts. Therefore, this paper takes the Everglades National Park, Florida (Excerpt) as an example to analyze the specific translation strategies and methods in applying Newmark's translation theory in tourism texts to provide references for other translators.